Prioritizing health information for national health reporting - a Delphi study of the Joint Action on Health Information (InfAct) - Angela Fehr; Stefanie Seeling; Anselm Hornbacher; Martin Thißen; Petronille Bogaert; Marie Delnord; Ronan A. Lyons; Mariken J. Tijhuis; Peter Achterberg; Thomas Ziese (BMC, 2022)
Abstract Background Health information (HI) strategies exist in several EU Member States, however, they mainly focus on technical issues and improving governance rather than on content-related priority setting. There is also little research available about national prioritization processes underlying HI development for policy support in the EU. The aim of this study was to broaden the knowledge base on HI prioritization strategies and to encourage expert exchange towards good practice models. A specific focus was put on HI produced for national health reporting, this being a crucial tool for policy advice. Methods We conducted a literature search to identify published and grey literature on national HI prioritization. This was followed by a two-round Policy Delphi study, where we explored which processes and methods exist in EU Member States and associated countries for the prioritization of HI collection. In the first round, information about these processes was gathered in semi-structured questions; in the second round, participants were asked to rank the identified approaches for desirability and feasibility. The survey was conducted online; participants were recruited from the membership of the Joint Action on Health Information (InfAct - Information for Action). Results 119 experts were contacted, representing 40 InfAct partner institutions in 28 EU Member States and associated countries. Of these, 28 experts responded fully or partially to the first round, and six to the second round. In the first round, more than half of the respondents reported the existence of structured HI prioritization processes in their countries. To prioritize HI, a clear preference was given in the second round for a formal, horizontal process which includes different experts and stakeholders. National public health institutes were named desirable key stakeholders in this process, and also desirable and feasible coordinators for stakeholder coordination. Conclusion Health information prioritization methods and procedures reflect the heterogeneity of national public health systems in European countries. Mapping, sharing and ranking prioritization methods and procedures for "good practices" provides a meaningful basis for expert knowledge exchange on HI development. We recommend to make this process part of a future sustainable EU health information system and to use the information gathered in this project to initiate the development of a guidance "Good Practice HI Prioritization" among EU Member States and associated countries.